+0  
 
0
108
2
avatar+121 

\(T(s) = \frac{G(s)}{1+N(s)G(s)}\)

 

if \(G(s) = \frac{10s}{(s+3)(s-2)}\)and \(N(s)=s+2\)

simplify the expression for T(s)

 

I'm in 2 minds about this...

 

I just want to cancel the G functions out on the top and bottom and then be left with, \(\frac{1}{1+(s+2)}\)

 

however my other brain is saying I need to do the arithmetic and see what I get.

vest4R  Mar 29, 2017
Sort: 

2+0 Answers

 #1
avatar+89781 
0

Mmm

 

\(T(s) = \frac{G(s)}{1+N(s)G(s)}\)

 

Immediately I a restraint  \(N(s)G(s)\neq -1\)

so

\((s+2)*\frac{10s}{(s+3)(s-2)}-1\ne0\\ 10s(s+2)-(s+3)(s-2)\ne0\\ 10s^2+20s-(s^2+s-6)\ne0\\ 10s^2+20s-s^2-s+6\ne0\\ 9s^2+19s+6\ne0\\ s\ne \frac{-19\pm\sqrt{145}}{18}\)

 

 

 

\(G(s) = \frac{10s}{(s+3)(s-2)}\\so\\ s\ne-3,\quad s\ne2 \\ N(s)=s+2 \)

 

 

\(T(s)=\frac{\frac{10s}{(s+3)(s-2)}}{ 1+(s+2)\frac{10s}{(s+3)(s-2)}}\\ T(s)=\frac{\frac{10s}{(s+3)(s-2)}}{ 1+(s+2)\frac{10s}{(s+3)(s-2)}}\times \frac{(s+3)(s-2)}{(s+3)(s-2)}\\ T(s)=\frac{10s}{(s+3)(s-2)+(s+2)10s}\\ T(s)=\frac{10s}{s^2+s-6+10s^2+20s}\\ T(s)=\frac{10s}{11s^2+21s-6}\quad where \;\;s\neq 2,-3,\frac{-21\pm\sqrt{705}}{22},\;or\;\frac{-19\pm \sqrt{145}}{18}\)

Melody  Mar 29, 2017
 #2
avatar+121 
0

thank you melody, I appreciate it

vest4R  Mar 29, 2017

3 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details